2001
DOI: 10.1614/0043-1745(2001)049[0022:rovdpt]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Response of velvetleaf demographic processes to herbicide rate

Abstract: Field studies were conducted in 1995 and 1996 to determine the rate response of velvetleaf seedling survival, seed production, and shoot biomass to postemergence herbicides in corn and soybean. Dicamba and imazethapyr were applied to corn and soybean, respectively, at 1, ½, ¼, ⅛, 1/16, 1/32, and 0× labeled rates. Velvetleaf mature plant density was linearly related to seedling density, thus indicating that seedling survival was not density dependent, even after seedling densities exceeded 150 plants m−2. Seedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 31 publications
4
44
0
Order By: Relevance
“…However, S. faberi biomass decreased with longer intervals, while C. album biomass either increased or remained unaffected. Previous research has shown a strong relationship between biomass and seed production for both species ( Bussan et al, 2000 ;Grundy et al, 2004 ), suggesting that increasing precipitation variation may impact the relative fi tness of these two species. The pronounced response of both species to interval length suggests that predicted changes in storm frequency and intensity ( Easterling et al, 2000 ;Weltzin et al, 2003 ;IPCC, 2007 ) could impact the overall abundance and species compo-[Vol.…”
Section: Discussionmentioning
confidence: 94%
“…However, S. faberi biomass decreased with longer intervals, while C. album biomass either increased or remained unaffected. Previous research has shown a strong relationship between biomass and seed production for both species ( Bussan et al, 2000 ;Grundy et al, 2004 ), suggesting that increasing precipitation variation may impact the relative fi tness of these two species. The pronounced response of both species to interval length suggests that predicted changes in storm frequency and intensity ( Easterling et al, 2000 ;Weltzin et al, 2003 ;IPCC, 2007 ) could impact the overall abundance and species compo-[Vol.…”
Section: Discussionmentioning
confidence: 94%
“…The use of sublethal herbicide dose could be promising as a strategy for decreasing the production costs and for environmental reasons, but results from other experiments indicate that this effect varies greatly, depending on the used herbicides and amount of weed species present in the fields (Bussan et al 2000, Zhang et al 2000. Results from the second year of our investigations are presented in Table 4 and Figure 2.…”
Section: Below Labelled Rates Of Herbicidesmentioning
confidence: 90%
“…Profitable, alternative weed management systems are therefore needed to help farmers to solve this pressing environmental concern without greatly changing current farming practice. However, despite of many successful examples (Buhler et al 1995, Zoschke 1994, concern over the use of herbicides at below-labelled rates remains (Bussan et al 2000, Zhang et al 2000.…”
mentioning
confidence: 99%
“…Bussan et al (2000) recorded seed production of up to 4000 seeds per plant in competition with soybean. In a soybean crop not treated with herbicides, the average seed production was about 600 seeds per plant (11 400 seeds m (2 ) (DeFelice et al 1989).…”
Section: Growth and Developmentmentioning
confidence: 99%